A Conceptual Framework on Need-Based Marketing and Entrepreneurship : A Strategic Pathway to Consumer-Centric Market Penetration - Patel, Vinod Kumar; Bargal, Hitendra; Gupta, Prashant (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : This paper attempted to construct and propose a conceptual model, which incorporated the needs-based marketing and entrepreneurial strategy to assist start-ups and small enterprises in sustainable market penetration and meaningful consumer interaction. The structure was created to meet the realistic consumer requirements based on the entrepreneurial responsiveness, direct market communication, and pricing mechanisms. Design/Methodology : The conceptual research design that was employed in the proposed study was based on the systematic review of the available literature on the areas of entrepreneurship, marketing strategy, and consumer behavior. The structure has been formulated by means of analytical thought and the incorporation of major theoretical frameworks such as customer-centricity, value-based pricing, and relationship marketing. The conceptual model was also depicted in a graphical manner to show the interaction between the five main elements, which include entrepreneurship, direct approach, competitive pricing, market penetration, and the consumer. Findings : The framework proved that entrepreneurs had great chances of increasing market penetration and consumer confidence through a direct and need-based approach that is reinforced by fair and competitive pricing. It put entrepreneurship at the center of the framework and was based on the belief that being responsive to consumer needs is more central to the inclusive and sustainable business success than a traditional product-based innovation. Practical Implications : It is a practical guide to entrepreneurs and business educators as well as policymakers. It helped to design the training programs, develop the marketing plans in the new markets, and develop the tools of community engagement among the startups. Moreover, the framework encouraged ethical entrepreneurial behavior that was based on empathy, accessibility, and long-term value-generation. Originality/Value : The study fulfilled a gap in the current literature of marketing and entrepreneurship by proposing a new interdisciplinary framework. The model was theoretically based and practically adaptable by connecting the consumer-oriented thinking and the entrepreneurial execution process to be relevant in various economic scenarios, specifically in the undermarked and emerging markets. The framework promoted the move of transactional business thinking to approaches of business practice that were more humane, inclusive, and effective.